Juridical Review of Criminal Sanction Enforcement In Immigration Law - Budiyanto, Budiyanto (LPPM Universitas Ekasakti Padang, 2024)
The aims of this research are: 1) to find out the modus operandi of criminal acts in the Immigration sector (Study of Decision Number 713/ Pid.Sus /2022/PN Mks ), 2) to find out how the judge considered in handling down Decision Number 713/ Pid.Sus /2022 /PN Mks. The type of research used by researchers is normative legal research using the statutory and case approaches. The research materials used as a base to support this research include primary and secondary legal materials and methods. The analysis is in the form of a prescriptive method, namely an analytical method that provides an assessment ( justification ) about whether the object under study is right or wrong or what should be according to the law. The conclusion in this research is The modus operandi carried out by the Defendant who committed a Crime in the Immigration Sectors in Decision Number 713/ Pid. Sus /2022/PN Mks was by burning his passport and travel documents in 2019 because they wouldn't be detected as foreigner citizens and are considered an Indonesian citizens. Where the Defendant Mohammed Abdulaziz Khamis Bin Sanad's passport expired in 2020, but continued to live and carry out activities in Indonesian Territory without having a passport, namely from February to October 2021, the Defendant worked for a Mining Company at PT Sungai Berlian Mahakam in Samarinda. On January 15, 2022, the defendant went to Makassar city to look for coffee and would export the coffee to Arabia. 2) The judge's legal considerations in imposing a sentence on the perpetrator of a crime in the field of immigration, as in Decision Number 713/ Pid.Sus /2022/PN Mks, where the Panel of Judges have handed down a decision on the Defendant by giving a prison sentence of 4 ( four ) months and 15 ( fifteen ) days and a fine of IDR 10,000,000.00 ( ten million rupiah). The decision of the Panel of Judges takes into account the facts revealed in the trials, and basically, the judge handed down the decision based on Law number 48 of 2009 concerning Judicial Power by paying attention to juridical and non-juridical considerations by paying attention to things that are aggravating and mitigation the Defendant.